Reprodutibilidade de metodologias métricas manuais e computadorizadas em antropologia forense - Silva, Herrison Félix Valeriano da (2023)
Osteometric methodologies in Forensic Anthropology are essential in the reconstruction of an individual's biological profile, being crucial that there is a correct execution and precision in the measurements, given the damage that inconsistencies may cause in the process of human identification. Therefore, the objective was to evaluate the reproducibility of manual and computerized osteometric methodologies, used in estimating population affinity, sex and height. To this end, the study had the participation of 15 dental students, who carried out 88 measurements recommended by the methods of estimating ancestry (AncesTrees®), gender (DSP2® and Wasterlain and Cunha, 2000) and height (Mendonça, 2000), in bone specimens from two different bones. Measurements were performed on dry bone and on tomographic images. At first, the measurements were performed only with the aid of a descriptive and illustrated manual. Subsequently, all measurements were redone, after theoretical-practical training. For the tomographic images, a theoretical-practical training was carried out on the handling of the image measurement software. Data were submitted to the respective estimation methods and subsequently compared. Shapiro-Wilk tests were performed for normality; 1-group and paired T tests, Intraclass Correlation Coefficient (ICC) and Kappa, for analysis of significance, analysis of inter- and intra-examiner agreement and comparison with the gold standard, in addition to the Bland-Altman test, for comparison between methods. For all analyses, a significance level of 5% was adopted. Among the examiners, in both bones, there was no statistically significant improvement in measurements after training. The intra-examiner agreement varied randomly regarding the bone analyzed. In the skull, before and after training, the same degree of agreement was obtained in only 02 measurements (FOL, DKB). Agreement was almost perfect in only 1 measurement (GOL) (4.0%), in bone 1, and in 22.0%, in bone 2. In the coxal bone, the predominant degree of agreement was median, with 70%, in frame 2, almost perfect was obtained in 20% of the measurements, in frame 1. In both frames, 20.0% of the measurements obtained insignificant agreement. In the long bones, differences were observed in the concordance of measurements related to sex and height. In terms of sex, there was a predominance of moderate and substantial degrees in bones 1 and 2, respectively. For height, the almost perfect degree of agreement was not observed and the PHLF and PLF measurements were not concordant in bone 2. The results of the analyzes of the estimation methods showed an improvement in the agreement between examiners, after training, in both bones, in ancestry and sex, with no difference for height. Accuracy was insignificant for ancestry and sex in bone frame 1 and median and almost perfect, respectively, in bone frame 2. Statistically significant differences were observed between manual and digital methods. It is concluded that basic anatomical knowledge has not proved to be synonymous with expertise in Forensic Anthropology, requiring a more rigorous leveling procedure so that the execution of metric methodologies is reliable, taking into account the anatomical nuances and taphonomic processes. In this sense, the inconsistencies between manual and digital measurements indicate the need for studies that develop specific parameters for locating osteometric points in tomographic images.